Stay Online : Student Teachers’ Views on Online Experiential Learning in Emergency Remote Teaching (ERT) - Piilikangas Assi; Lindfors Eila (Universitetsbiblioteket OsloMet, 2022)
The COVID-19 pandemic provided us with a living laboratory to study emergency remote teaching (ERT) when its emergence forced teaching to migrate from face-to-face to online in Finland, as in many parts of the world. This paper examines student teachers’ perceptions of the usability of online teaching from their experiential learning viewpoint. The student teachers (N=20) were enrolled in the Introduction to Craft, Design and Technology (CDT) in Primary Education course and were asked to participate in a survey with open-ended questions. CDT education aims to facilitate experiential learning using hands-on design, building and engineering. Kolb’s cycle models experiential learning as a combination of experiences, perceptions and conceptualisations through active learning, and the elements of active learning, from a student’s point of view, can be considered elements of usability, e.g., the elements of online teaching the students consider valuable and meaningful in their active learning. The analysis criteria for usability were drawn from a literature review, and theory-driven content analysis was applied. The results, consistent with prior research, indicate that flexibility and independence are seen as positive and that the change in teaching methods, increased workload and lack of social contact are seen as negative in online ERT.